2011
DOI: 10.2147/ijicmr.s10200
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti-inflammatory drugs: prostaglandins, indications, and side effects

Abstract: For centuries, nonsteroidal anti-inflammatory drugs (NSAIDs) have been part of our clinical practice. They started out as drugs with anti-inflammatory and analgesic action, and gradually their use has been expanded to new therapeutic targets, some of which are unrelated to their primary mode of action. Today, our armamentarium includes a large range of compounds, attesting to their utility in the treatment of clinical pathologies ranging from pain and inflammation to prevention and treatment of cancer. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 83 publications
(135 reference statements)
0
56
1
2
Order By: Relevance
“…Evidently, the most common side effect of NSAIDs use is gastrointestinal toxicity, which is the primary limiting factor for their use [10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the most common side effect of NSAIDs use is gastrointestinal toxicity, which is the primary limiting factor for their use [10][11].…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance results in high blood pressure and risk of thrombus formation, which tend to increase with the progression of the treatment, with a higher incidence of ischemic events after a few months of use of these drugs [7,8,9].…”
Section: Coxibs In Dentistry: An Updatementioning
confidence: 99%
“…Such events are a result of this selectivity that provides an unbalance between anti-and pro-thrombotic factors, with the action of thromboxane (TXA2) predominating at the expense of prostacyclin (PGI2), a potent vasodilator and platelet anti-aggregant, which triggers a series of cardiovascular complications. Among these drugs are the celecoxib, etoricoxib, valdecoxib, parecoxib and lumiracoxib [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Many synthesis in inflamed tissues [28,29]. Other studies have demonstrated 49 that endogenous opioids and the NO/cGMP/KATP pathway may be 50 involved in the antinociceptive mechanisms of NSAIDs [2,20,25,31].…”
mentioning
confidence: 99%
“…inhibition of cyclooxygenase activity and thus decreased 189 prostaglandin synthesis[28]. However, the profiles of the analgesic190 activities of dipyrone and diclofenac differ from those of other common 191 NSAIDs due to their direct antagonistic effects on PGE 2 -induced 192 hyperalgesia.…”
mentioning
confidence: 99%